A Classification Idiomatic Expression in Taylor Swift by Song Lyric - Riva Oktamevia; Siva Nur Aisyah; Faisal (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This article examines the intricate use of language in Taylor Swift’s critically acclaimed album Red, with a particular emphasis on idiomatic expressions as a medium of communication and artistic expression. Language serves as a fundamental instrument of human interaction, allowing individuals to articulate nuanced thoughts, emotions, and personal experiences. Through the lens of idiomatic language, this study explores how figurative expressions contribute to the emotional depth and narrative power of song lyrics. Using a qualitative descriptive approach, the research analyzes selected tracks from the album to identify various idioms, classify their types, and interpret their contextual meanings. The analysis reveals that idiomatic expressions are not only stylistic devices but also key components in constructing relatable and emotionally resonant messages for the audience. Moreover, the study highlights how Swift’s lyrical choices reflect broader cultural and linguistic patterns, illustrating the interplay between personal storytelling and universal themes. Ultimately, the findings underscore the significance of idioms in enhancing the poetic and communicative dimensions of popular music, positioning language as both an expressive and interpretive force in the domain of contemporary songwriting.